The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2012
DOI: 10.1159/000338281
|View full text |Cite
|
Sign up to set email alerts
|

Altered Serum Levels of Brain-Derived Neurotrophic Factor in Patients with Pathological Gambling

Abstract: Background: Brain-derived neurotrophic factor (BDNF) plays important roles in neurotransmitter release and synaptic plasticity and has been hypothesized to be involved in the development and maintenance of addictive disorders. The objective of this study was to investigate alterations of BDNF expression in a non-substance-related addiction, i.e. pathological gambling (PG). Methods: Serum levels of BDNF were assessed in male patients with PG (n = 14) and healthy control subjects (n = 13) carefully matched for s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
18
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 76 publications
(45 reference statements)
3
18
0
Order By: Relevance
“…BDNF seems likely to play a role in addiction for other reasons also. For example, BDNF serum levels are increased in individuals with addictive behaviors such as pathological gambling (Geisel et al, 2012) and opiate dependence (Heberlein et al, 2011). Serum levels of BDNF are also elevated in naïve individuals following exposure to Δ 9 -tetrahydrocannabinol (THC), the main psychoactive component in marijuana, a commonly abused drug (D’Souza et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…BDNF seems likely to play a role in addiction for other reasons also. For example, BDNF serum levels are increased in individuals with addictive behaviors such as pathological gambling (Geisel et al, 2012) and opiate dependence (Heberlein et al, 2011). Serum levels of BDNF are also elevated in naïve individuals following exposure to Δ 9 -tetrahydrocannabinol (THC), the main psychoactive component in marijuana, a commonly abused drug (D’Souza et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have reported that BDNF is elevated in patients with pathological gambling ( Angelucci et al., 2013 ; Choi et al., 2016 ; Geisel, Panneck, Hellweg, Wiedemann, & Müller, 2015 ). Researchers have suggested that the increased BDNF in pathological gamblers is related to altered dopaminergic transmission in the ventral tegmental area and nucleus accumbens, which are central components of the brain’s reward system ( Geisel, Banas, Hellweg, & Müller, 2012 ; Pu, Liu, & Poo, 2006 ).…”
Section: Introductionmentioning
confidence: 99%
“…While the reward deficiency hypothesis states that addiction is associated with diminished striatal value signals ( 16 ), an idea supported by some studies ( 17 19 ), other studies have found the opposite effect ( 20 , 21 ). PG has been associated with higher levels of brain-derived neurotrophic factor (BDNF), which regulates midbrain dopamine release ( 22 , 23 ). This effect was not associated with addiction severity ( 22 ).…”
Section: Introductionmentioning
confidence: 99%
“…PG has been associated with higher levels of brain-derived neurotrophic factor (BDNF), which regulates midbrain dopamine release ( 22 , 23 ). This effect was not associated with addiction severity ( 22 ). Monetary rewards might affect the reward system of PGs differently depending on the context and that the relation to non-monetary rewards is important.…”
Section: Introductionmentioning
confidence: 99%